An Examination of Stalking Experiences During Military Service Among Female and Male Veterans and Associations With PTSD and Depression. Issue 21 (November 2021) - Lucas, Carrie L.; Cederbaum, Julie A.; Kintzle, Sara; Castro, Carl Andrew
Stalking is associated with mental health concerns, although little is known about the influence of stalking and mental health concerns among veterans. This study evaluated stalking experienced during military service in two community-based, nonclinical samples of veterans ( N = 1, 980). Models explored (a) types of stalking, (b) characteristics of veterans who experienced stalking, and (c) the associations between stalking with posttraumatic stress disorder (PTSD) and depression. Types of stalking varied by sex; female veterans were significantly more likely to experience stalking than male veterans (58.5% vs. 34.6%, p < .001, respectively). Female veterans reported unwanted messages, emails, or phone calls (37.2%), and male veterans experienced someone showing up unannounced or uninvited (23.5%) most frequently. Stalking experiences also differed by age with female and male veterans 18 to 39 years old significantly more likely to have experienced stalking ( p < .001 and p < .001, respectively) than veterans over age 40. Associations between prior stalking experiences and mental distress were found for both female and male veterans. Both female and male veterans who experienced stalking were significantly more likely to have probable PTSD (odds ratio [OR] = 1.88, 95% confidence interval [CI] = [1.04, 3.39] and OR = 3.08, 95% CI = [2.27, 4.18], respectively) and depression (OR = 2.54, 95% CI = [1.38, 4.58] and OR = 2.78, 95% CI = [2.05, 3.79], respectively). These findings highlight (a) the rates of stalking experienced during military service, (b) the need for assessment of stalking to inform treatment, and (c) lay the foundation for the Department of Defense (DoD) to further evaluate stalking among military populations.